Chinese transnational investment in Australia: a case study of insider/outsider relations - Forbes-Mewett, Helen; Nyland, Chris; Thomson, Stanley Bruce (My University, 2013)
Against the backdrop of a nation where more than a third of the population is concerned about cultural differences threatening societal harmony, we explore community responses to a proposed development by a Chinese transnational company. An alumina refinery was to be built in Utopia, a small coastal town in North Queensland, Australia. Framed within the dimensions of Elias and Scotson’s notion of established and outsider relations, we reveal the complexities of a community that consisted largely of a group of long-term residents (the Established) and a newer group who have lived in the town for periods up to three years (the Entrepreneurs). Together they faced the prospect of another group moving into the community-the Chinese. The concerns of the community related to assimilation, employment and the natural environment revealing cultural issues that are the hallmark of new racism.
Keywords: insider/outsider; new racism; transnational investment; TNC